INNOVATIVE APPROACHES TO THE FORMATION OF LEATHERS WITH HYDROPHOBIC PROPERTIES - HORBACHUK , OLESIA; MOKROUSOVA, OLENA; SKYBA , MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The aim of this study was to substantiate the features of innovative approaches to the formation of leathers with hydrophobic properties. A comparative analysis of scientific research revealed innovative approaches to the formation of leathers with hydrophobic properties. The study generalized innovative directions for achieving hydrophobicity, including the influence of fatliquoring agents and synthetic polymers during the post-tanning treatment of chrome-tanned semi-finished items; the influence of synthetic polymers during the finishing of the leather's  grain surface; and the influence of technological treatments for applying hydrophobic materials to the surface and  structural elements of the leather. Innovative approaches to the formation of hydrophobic leathers are associated with improving technologies for the use of synthetic polymeric materials in combination with various modifiers. To achieve a high level of  hydrophobization of leathers, the effective use of a complex approach with sequential treatment with synthetic fatliquoring materials and synthetic polymeric materials at the post-tanning stage has been proven, and to enhance the waterproofing effect, it is recommended to apply a hydrophobic protective coating based on polymer composites. The prospects of implementing modern technical solutions such as plasma technologies and sol-gel treatments to increase the efficiency of hydrophobization and maintain the hygienic characteristics of leathers for military footwear have been determined. A comprehensive analysis of innovative approaches to the formation of leathers with hydrophobic properties will allow analyzing ways to achieve hydrophobicity of leathers and develop new technologies for processing leathers, more efficiently using domestic raw materials and reducing dependence on imports. The developed leathers will provide an optimal microclimate in footwear, contributing to the comfort and health of the military.
Keywords: leather; hydrophobicity; fatliquoring; waterproofing; leather coating finishing; plasma technologies